2007
DOI: 10.1007/s00592-007-0252-8
|View full text |Cite
|
Sign up to set email alerts
|

Soybean oil treatment impairs glucose-stimulated insulin secretion and changes fatty acid composition of normal and diabetic islets

Abstract: We investigated the effect of sub-chronic soybean oil (SO) treatment on the insulin secretion and fatty acid composition of islets of Langerhans obtained from Goto-Kakizaki (GK), a model of type 2 diabetes, and normal Wistar rats. We observed that soybean-treated Wistar rats present insulin resistance and defective islet insulin secretion when compared with untreated Wistar rats. The decrease in insulin secretion occurred at all concentrations of glucose and arginine tested. Furthermore we observed that soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
2
15
0
1
Order By: Relevance
“…Additionally, these authors suggest that treatment with SB oil induces insulin resistance in normal rats by analyzing the HOMA index. 19 According to this study, we now demonstrate that SB decreases insulin sensitivity as assessed by the analysis of ITT. Moreover, the present study demonstrates that, as an example of the SB oil, treatment with SF oil also causes insulin resistance in normal rats.…”
Section: Metabolic Parametersmentioning
confidence: 82%
“…Additionally, these authors suggest that treatment with SB oil induces insulin resistance in normal rats by analyzing the HOMA index. 19 According to this study, we now demonstrate that SB decreases insulin sensitivity as assessed by the analysis of ITT. Moreover, the present study demonstrates that, as an example of the SB oil, treatment with SF oil also causes insulin resistance in normal rats.…”
Section: Metabolic Parametersmentioning
confidence: 82%
“…Culture of islets with soybean oil or its free fatty acid constituents can induce apoptosis and reduce insulin secretion. [61][62][63][64] Soybean oil could be especially deleterious at the high local concentration used in this study and may account for the limited cell death observed at the islet periphery. The high concentration of egg yolk phospholipid surfactants might also be toxic.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose tolerance test was performed 3 days before sacrifice. Plasma insulin was determined by an in-house competitive enzyme-linked immunosorbent assay (ELISA), as previously described [14,15] …”
Section: Blood Glucose and Plasma Insulin Levelsmentioning
confidence: 99%